Formulation Development and Evaluation of Sodium Bicarbonate Tablets by Direct Compression Method - Sadia Mehrban,; Fouzia Hassan,; Syed Muhammad Farid Hasan,; Fozia Israr,; Sabahat Jabeen ,; Naheed Haque, (Journal of Basic & Applied Sciences, 2013)
Acidity is a worldwide problem caused by an imbalance between the acid secreting mechanisms of stomach and proximal intestine. It creates great trouble in the life of many people. An antacid neutralizes excess acidity and provide relief. Sodium bicarbonate is prescribed as an antacid to treat heartburn and acid indigestion condition. The main objective of the current work was to prepare sodium bicarbonate antacid tablets by direct compression method and to evaluate trial formulation with those available in the local market by pharmacopeial and nonpharmacopeial methods. Besides sodium bicarbonate, the excipients used were lactose, microcrystalline cellulose (Avicel) and magnesium stearate. The tablet weight set for compression was 318mg (±5%). After sieving through a 20 mesh screen, the powder was blended for five minutes and evaluated for its flow properties before compression on a single punch machine. The results revealed that the blend possessed good flow property, compressed easily and the resulting tablets complied all the standards and showed a close resemblance with sodium bicarbonate tablets which are available in the local market.